Development of the theory-based Chinese primary school children physical activity and dietary behaviour changes intervention (CHIRPY DRAGON): development of a cluster-randomised controlled trial. (October 2016) - Li, Bai; Liu, Wei Jia; Cheng, Kar Keung; Pallan, Miranda; Hemming, Kalar; Frew, Emma; Lin, Rong; Liu, Wei; Adab, Peymane
Abstract: Background: The rate of increase in prevalence of childhood obesity in mainland China exceeds the trends observed in other countries. Effective, culturally appropriate prevention interventions are urgently needed to control the epidemic. However, previous programmes lacked rigorous development and evaluation. Using the framework set out by the UK Medical Research Council (MRC), we developed a complex childhood obesity prevention intervention for Chinese primary school children. Methods: Several different methodologies were employed and iteratively combined in the development process. The theoretical and modelling phases (2009–12) included a mixed-methods study that integrated focus groups and interviews with key stakeholders (n=99) to explore perceived causes of childhood obesity and perceptions of effective and feasible intervention ideas as well as delivery preferences, and a cross-sectional study (n=497) that identified several modifiable environmental risk factors. This phase resulted in six potential intervention targets that were evidenced in both studies. A further qualitative study (2012–14, n=148) gathered key stakeholders' opinions on the potential interventions with a focus on contextual barriers and facilitators. A systematic review of international and Chinese literature in modifiable risk factors for obesity in Chinese children was also conducted. These investigations led to the development of an initial programme that was then tested for feasibility in three Chinese primary schools in 2015. The feasibility trial justified an evaluation of the programme in a definitive trial and helped to optimise the implementation and acceptability of the programme. Ethical approval was obtained from the Life and Health Sciences Ethical Review Committee at the University of Birmingham (ERN_14-1440) and the Ethical Committee of Guangzhou Centre for Disease Control and Prevention. The feasibility and randomised control trials were registered with ISRCTN, numbers ISRCTN13619480 (feasibility) and ISRCTN11867516 (randomised controlled trial). Findings: The finalised programme consists of four components: 1) improving health knowledge and behaviours among grandparents/parents and children through interactive learning activities; 2) improving the nutritional quality of school meals through regular supportive evaluation and feedback; 3) increasing the level of physical activity outside campus through family friendly games and challenges; and 4) improving the implementation of the national requirement for "one-hour physical activity on campus each day" through joint monthly goal settings, evaluation, and feedback. Interpretation: Our study is the first demonstration of application of the MRC framework to develop and evaluate obesity prevention interventions in a Chinese setting. The rigorous and phased development process resulted in a culturally relevant prevention programme for urban Chinese children. The programme is ready for effectiveness and cost effectiveness evaluations through a definitive trial. We also generated contextual knowledge that could support implementation of similar intervention activities in other settings. Funding: University of Birmingham, Zhejiang Yong Ning Pharmaceutical.